Uniqueness theorems for algebraic functions that take the number of algebraic elements into account - Gol'dberg, A. A.; Гольдберг, А. А.; Гольдберг, А. А. (Institute of Mathematics, NAS of Ukraine, 1995)
We obtain uniqueness theorems for algebraic functions that take into account not only A-points but also the number of covering elements located above them.